Isolation and biological evaluation 7-hydroxy flavone from Avicennia officinalis L: insights from extensive in vitro, DFT, molecular docking and molecular dynamics simulation studies. Issue 7 (3rd May 2023) - Parthiban, A.; Sachithanandam, V.; Lalitha, P.; Elumalai, Dhanasekar; Asha, Radhakrishnan Nandini; Jeyakumar, Thayalaraj Christopher; Muthukumaran, J.; Jain, Monika; Jayabal, Kamalraja; Mageswaran, T.; Sridhar, R.; Purvaja, R.; et al.
Abstract: The flavonoid based 7-hydroxy flavone (PubChem CID: 5281894; molecular formula: C15 H10 O3 ) molecule has been isolated for the first time from the methanolic extract from the leaves of Avicennia officinalis L. in the tropical mangrove ecosystem of Andaman and Nicobar Islands (ANI), India. The molecular structure of bioactive compound was characterized by spectroscopic analysis, including FT-IR, 1 H, 13 C NMR spectroscopy and ESI-HRMS and elucidated as 7-hydroxy flavone. An anticancer activity of isolated 7-hydroxy flavone was evaluated by in vitro study against two different human cancer cell lines namely, HeLa (cervical cells) and MDA-MB231 (breast cells) and they exhibited promising anticancer activity with IC50 values are 22.5602 ± 0.21 µg/mL and 3.86474 ± 0.35 µg/mL, respectively. The antioxidant property of 7-hydroxy flavone at a standard concentration of 50 µg, was found to be (IC50 ) 5.5486 ± 0.81 µg/mL. In summary, this investigation provides evidence that 7-hydroxy flavone exhibits both anticancer and antioxidant properties. Meanwhile, the antimicrobial activity ability of 7-hydroxy flavone were also evaluated using three Gram positive and two Gram negative strain exhibited no antimicrobial activities. Density-functional theory (DFT) studies confirm the structure is global minima in the PES, from the optimized geometry FMO and MESP map analyzed. Further, the molecular docking and molecular dynamics simulation studies result shows that 7-hydroxy flavone has the better binding ability with anti-apoptotic Bcl-2 protein with the estimated free energy of binding of –6.3 kcal/mol. This bioactive compound may be act as drug candidate for treating various kinds of cancers. Highlights: A 7-hydroxy flavone molecule has been isolated from Avicennia officinalis . The isolated pure compound was subjected to spectral analysis such as FT-IR, 1 H NMR, 13 C NMR spectral data and HRMS analysis for skeleton of the molecule. The anticancer activity of 7-hydroxy flavone studied against Cervical (HeLa) cancer cell lines and breast (MDA-MB231) cancer cell lines with the IC50 values of 22.5602 ± 0.21 µg/mL and 3.86474 ± 0.35 µg/mL), respectively. The antioxidant properties of 7-hydroxy flavone were found to be (IC50 ) 5.5486 ± 0.81 µg/mL at a standard concentration of 50 µg. DFT, molecular docking and MD simulation results explained that 7-hydroxy flavone could be the most promising candidate to inhibit the function of anti-apoptotic Bcl-2 protein in cancerous cell. Communicated by Ramaswamy H. Sarma